Regulatory T cells infiltrate the tumor-induced tertiary lymphoïd structures and are associated with poor clinical outcome in NSCLC - Devi-Marulkar, Priyanka; Fastenackels, Solène; Karapentiantz, Pierre; Goc, Jérémy; Germain, Claire; Kaplon, Hélène; Knockaert, Samantha; Olive, Daniel; Panouillot, Marylou; Validire, Pierre; Damotte, Diane; Alifano, Marco; et al. (Communications biology, 2022)
On one hand, regulatory T cells (Tregs) play an immunosuppressive activity in most solid tumors but not all. On the other hand, the organization of tumor-infiltrating immune cells into tertiary lymphoid structures (TLS) is associated with long-term survival in most cancers. Here, we investigated the role of Tregs in the context of Non-Small Cell Lung Cancer (NSCLC)-associated TLS. We observed that Tregs show a similar immune profile in TLS and non-TLS areas. Autologous tumor-infiltrating Tregs inhibit the proliferation and cytokine secretion of CD4 + conventional T cells, a capacity which is recovered by antibodies against Cytotoxic T-Lymphocyte-Associated protein-4 (CTLA-4) and Glucocorticoid-Induced TNFR-Related protein (GITR) but not against other immune checkpoint (ICP) molecules. Tregs in the whole tumor, including in TLS, are associated with a poor outcome of NSCLC patients, and combination with TLS-dendritic cells (DCs) and CD8 + T cells allows higher overall survival discrimination. Thus, Targeting Tregs especially in TLS may represent a major challenge in order to boost anti-tumor immune responses initiated in TLS. Regulatory T cells (Tregs) have similar immune profiles in tertiary lymphoid structures of lung cancer and non-TLS areas, with tumor-infiltrating Tregs found to inhibit the proliferation and cytokine secretion of CD4 + conventional T cells.